ASSESSMENT OF THE EFFECTIVENESS OF STATE BUDGET DISTRIBUTION (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In an era of increasing interconnectedness and shared global challenges, the efficiency of government budget allocation is a key determinant of economic prosperity and social well-being on a global scale. The allocation of financial resources by governments not only reflects their fiscal policies, but also shapes the trajectory of development, meeting diverse needs such as infrastructure, education, health and social welfare. The purpose of this study is to shed light on the nuances of public budget allocation efficiency in a global context where countries face different economic structures, political systems and social needs.As countries navigate the complexities of the modern era, understanding the efficiency of government budget allocation becomes paramount. The consequences of budget decisions extend far beyond national borders, affecting global economic stability and sustainable development.